The complete mitochondrial genome of the Dongan black chicken and its phylogenetic analyses. Issue 2 (3rd July 2018) - Peng, Si-Min; Lin, Qian; Jiang, Gui-Tao; Li, Ying-Hui; Dai, Qiu-Zhong; He, Xi; Yan, Hai-Feng
Abstract: Dongan black chicken ( Gallus gallus domesticus, DBC) is one of the famous native breed of Hunan province in China. The complete mitochondrial genome sequence plays an important role in the accurate determination of phylogenetic relationships among metazoans. It is the first time that the complete mitochondrial genome sequence of the DBC was reported. The total length of the mtDNA is 16, 785 bp, It contains the typical structure, including 22 transfer RNA genes, 2 ribosomal RNA genes, 13 protein-coding genes and 1 non-coding control region (D-loop region). The overall composition of the mtDNA was estimated to be 30.27% for A, 23.78% for T, 32.46% for C, and 13.49% for G. Phylogenetic analyses using N-J computational algorithms showed that the analyzed 21 Galliformes species are divided into four major clades: Phasianidae, Numidiidae, Odontophoridae, and Megapodiidae. In addition, our work confirmed that DBC and Taoyuan chicken (TYC) have a close genetic relationship with fellow tribal members Xuefeng black-boned chicken (XBC) and Huang Lang chicken (HLC). Meanwhile, we also found that DBC and TYC have highly similar genetic relationship. This work will provide an important data set for the study of genetic mechanism of chicken in Hunan province.